Training, Research and Development, and Spillover Effects of Foreign Direct Investment: A Study on Labour Productivity in Malaysian Manufacturing Industry - Norhanishah Mohamad Yunus; Fazelina Sahul Hamid (International Journal of Supply Chain Management, 2019)
Using 2-digit levels of panel data set from 16 manufacturing industries during the period of 2000-2014, the present study adds to the literature by presenting new evidence at the industry level. We investigated the impact of training and research and development (R&D) investments jointly with the spillover effects of Foreign Direct Investment (FDI) in influencing labour productivity in Malaysian manufacturing industry. We employed the ordinary least square (OLS) estimator using regression with a robust standard error to estimate the labour productivity model. Our results clearly showed that investment in training is important in increasing labour productivity. It is interesting to highlight that when FDI spillovers from both â€œlearningâ€ and â€œtechnologyâ€ effects are taken into account in the labour productivity function, R&D investment showed a positive and significant impact on labour productivity. However, more important findings to be reported is that the spillover effects of FDI appear to be quickly assimilated by workers in the Malaysian manufacturing industries through the